A critical review of the literature on comfort of hearing protection devices: analysis of the comfort measurement variability. Issue 1 (2nd January 2022) - Doutres, Olivier; Sgard, Franck; Terroir, Jonathan; Perrin, Nellie; Jolly, Caroline; Gauvin, Chantal; Negrini, Alessia
Abstract : Objective . This article proposes a comprehensive literature review of past works addressing hearing protection device (HPD) comfort with the aim of identifying the main sources of variability in comfort evaluation. Methods . A literature review of study samples was performed: documents were hand searched and Internet searched using PubMed, Web of Science, Google Scholar, ProQuest Dissertations and Theses Professional, Scopus or Google search engines. While comfort constructs and measurement methods are reviewed for both earplugs and earmuff HPD types, results and analyses are provided for earplugs only. Results . The literature shows that the multiple sources of the perceived comfort measurement variability are related to the complexity of the concept of comfort and to the various physical and psychosocial characteristics of the triad 'environment/person/earplug', which differ from one study to the other. Conclusions . Considering the current state of knowledge and in order to decrease comfort measurements variability, it is advised to: (a) use a multidimensional construct of comfort and derive a comfort index for each comfort dimension;, (b) use exhaustive and valid questionnaires; (c) quantify as many triad characteristics as possible and use them as independent or control variables; (d) assess the quality of the earplug fitting and the attenuation efficiency.